Interobserver agreement on definition of the target volume in stereotactic radiotherapy for pancreatic adenocarcinoma using different imaging modalities - Gkika, Eleni; Kostyszyn, D.; Fechter, Tobias; Moustakis, C.; Ernst, F.; Boda-Heggemann, Judit; Sarria, G.; Dieckmann, K.; Dobiasch, S.; Duma, M. N.; Eberle, F.; Kroeger, K.; et al. (Strahlentherapie und Onkologie, 2023)
The aim of this study was to evaluate interobserver agreement (IOA) on target volume definition for pancreatic cancer (PACA) within the Radiosurgery and Stereotactic Radiotherapy Working Group of the German Society of Radiation Oncology (DEGRO) and to identify the influence of imaging modalities on the definition of the target volumes.
Online veröffentlicht: 2. Juni 2023
Gesehen am 14.08.2024